2015
DOI: 10.5603/fm.a2018.0036
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the vertebral artery origin and transverse foramen entrance level — CT angiographic study

Abstract: Vertebral artery (VA), the main element of the posterior brain circulation, has many anatomical variations which generally were widely investigated. However, available data vary in wide ranges, reflecting very different sample sizes, lack of data about left-right or sex differences, and about possible ethnic, regionally specific or genetic differences. Certain new findings suggest possible involvement of some environmental factors in VA variations. Accurate anatomical data about VA variations in different regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 11 publications
(29 reference statements)
1
19
0
Order By: Relevance
“…The incidence in the current study (6.9%) is similar to previous cadaveric report from South African population (8.5%) (Doctoral dissertation, University of Cape Town). Our result is also comparable to recent reports that used similar imaging modalities (CTA) in an Egyptian population (7%) [ 1 ] but slightly higher than reports from Republika Srpska population (4.47%) [ 40 ] and Turkish population (3.6%) [ 2 ]. In the present study, the comparison of the incidence across the racial groups showed that variation in origin is highest in White (3.6%), followed by Indian (2.5%) and least in Black (0.7%) South African.…”
Section: Discussionsupporting
confidence: 90%
“…The incidence in the current study (6.9%) is similar to previous cadaveric report from South African population (8.5%) (Doctoral dissertation, University of Cape Town). Our result is also comparable to recent reports that used similar imaging modalities (CTA) in an Egyptian population (7%) [ 1 ] but slightly higher than reports from Republika Srpska population (4.47%) [ 40 ] and Turkish population (3.6%) [ 2 ]. In the present study, the comparison of the incidence across the racial groups showed that variation in origin is highest in White (3.6%), followed by Indian (2.5%) and least in Black (0.7%) South African.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to supplying the spinal cord, the vertebral arteries also feed the brainstem and posterior regions of the brain. Anatomical variations—including lateral loops, different origins, course variations through the craniocervical junction, and accessory vessels of the vertebral artery—have been previously reported in the literature with imaging techniques and anatomical dissections (7,8).…”
Section: Discussionmentioning
confidence: 93%
“…Of these we selected 91 adult persons (182 VAs) of both sexes (47 males and 44 females) and of age between 33 and 75 years (Table 1) for the study of VA diameters. From the study were excluded the patients with abnormal morphology of VA, with unusual anatomical features (variations of origin described previously [26], kinking and coiling) or with previous or current cerebrovascular accidents, with injuries of cervical region, vertebrobasilar insufficiency, atherosclerotic changes of vessels (affecting more than 50% of VA diameter), with developmental abnormalities of cervical spine and with severe spondyloarthrosis. The patients were selected according to the described criteria, and only those of so selected patients who also gave informed consent (91 patients) were finally included in this study.…”
Section: Methodsmentioning
confidence: 99%